Physical Disintegration Characterization of Mudrocks Subjected to Slaking Exposure and Immersion Tests - Sadisun, Imam A.; Bandono, Bandono; Shimada, H.; Ichinose, M.; Matsui, K. (Geological Agency, 2010)
DOI:Â 10.17014/ijog.v5i4.105In order to gain insights into the detailed physical disintegration characteristics of various types of mudrock, a series of static slaking exposure and immersion tests were carefully carried out in this study. The intent of this paper is to exhaustively describe and discuss the results of the tests, including slaking mechanism, mode and rate/intensity. In general, it can be obviously identified that there are significant different susceptibilities of each mudrock tested to slake-disintegration. These differences can not only be identified from the results of slaking exposure test but also from slaking immersion test. It seems that there is also an agreement in both testing results, which show that the most resistant mudrock to slaking was Ikeshima shales, and was comparatively, followed by Ombilin siltstones, Tanjung Enim mudstones-claystones, and Subang claystones as the worst slaking characteristic. The detailed differences in fundamental characteristics of physical disintegration characteristics will further widely be discussed in this paper.